The project managers and relation with I.R 4.0(Industrial Revolution 4.0) tools to overcome and solution to the problem of delay for Malaysian construction project - Mohd Sa’ad, Mohd Haris; Herman, Siti Sarah; Azlan, Aznida (Faculty of Management & Muamalah, International Islamic University College Selangor, 2022)
In this Industrial Revolution 4.0 (I.R 4.0) era, the participation of government bodies like Public Work Department (PWD/JKR), Construction Industrial Development Board (CIDB), professional body Contractor Service Center (PKK), along with independent body like Board of Engineers (BOE), Board of Architect (BOA), Board of Quantity Surveyor (BQSM), as well as private consultants and contractors, is primarily crucial in solving and finding possible solutions on how to mitigate problems that occur in construction projects. This research will cover the subtopic of the detection of difficulties in construction projects, which is directly related to the main subject of delay. The research focus as qualitative mixed-method and 150 respondents were chosen randomly from construction industry background and due to pandemic Covid-19 restriction, only 43 of them responded to participate for semi-structured interview and a google form questionnaire. The responses are from Klang's Valley construction industry. The google form was distributed by email using Likert scale with level 1-4 and validation of data by SPSS software is employed in this research's. The semi-structured interview were conducted via tele-conversation and transcripted where later transferred to Nvivo software for validation.Lack on communication is the major findings The contribution of I.R.4.0 to government bodies, private sector and education are about time saving on communication and fast action on mitigating the problems for construction industry. For future research, the suggestion for the observation and grounded theory to be conducted for more depth information.